The Correlation Between Adherence to Antihypertensive Drug Use and Quality of Life in Hypertensive Patients at Haji Medan General Hospital - Arisya Permata Syarie; Melviana Lubis (Journal of Social Research, 2025)
The World Health Organization (WHO) states that around 972 million people or 26.4% of people in the world suffer from hypertension, this figure is likely to increase to 29.2% in 2025. There are 972 million people with hypertension, 333 million are in developed countries and the remaining 639 are in developing countries, one of which is Indonesia. Based on data from the Indonesian Ministry of Health in 2018, the prevalence of hypertension in Indonesia was recorded at 658,201 million people. Hypertension treatment is a lifelong treatment, but what happens is that treatment compliance is less than optimal because there are people with hypertension who do not routinely take their medication. According to previous research, the level of compliance with taking medication is low (60%), moderate (31%), and high (9%). Objective: To determine the relationship between compliance with the use of antihypertensive drugs and the quality of life of hypertension sufferers at the Haji Medan General Hospital. Objective To determine the relationship between compliance with the use of antihypertensive drugs and the quality of life of hypertension patients at the Haji General Hospital, Medan. Methods: The sample used was 60 patients who met the inclusion and exclusion criteria, then the patients filled out the antihypertensive therapy adherence questionnaire using the MMAS-8 and the quality of life questionnaire using the WHOQoL-BREF. Results: In this study, the Chi Square value was found to be 0.000, which is smaller than 0.005, so it can also be concluded that there is a relationship between Compliance with the Use of Antihypertensive Drugs and the Quality of Life of Hypertension Patients at the Haji General Hospital, Medan.